Sex differences in miRNA as therapies for ischemic stroke. (July 2019) - Sohrabji, Farida; Selvamani, Amutha
Abstract: MicroRNAs, a subset of non-coding RNAs, are present in virtually all tissues including body fluids and are global regulators of the transcriptome. In view of the expanding number of microRNAs and the large number of gene targets that each microRNA can potentially regulate, they have been compared to hormones in the scope of their effects. MicroRNA have been implicated as biomarkers for several diseases including stroke, as well as chronic conditions that are associated with stroke. Recent research has focused on manipulating miRNA to improve stroke outcomes. Although several miRNAs have been shown to have neuroprotective properties, the overwhelming majority of these studies have employed only male animals. This review will focus on two miRNAs, Let7f and mir363–3p, whose effectiveness as a stroke neuroprotectant is sex-specific. Highlights: In experimental studies, miRNA therapy after ischemic stroke has been shown to improve histological and behavioral outcomes. With few exceptions, most of these studies have been performed only on male animals. This review focuses on two microRNAs, Let7f and mir363–3p, that are affected by age and biological sex. Anti-Let7f and mir363–3p show sex-specific effects, namely, they are neuroprotective in female but not male rats.